Effects of Frost Mulberry Leaf Superfine Powder on the Hypoglycemic and Gut Microbiota of High-Fat Diet/Streptozotocin-Induced Type 2 Diabetes Mellitus Mice - Jingya Wu; Qiu Wu; Guojian Zhao; Jing Liang; Lei Sun; Ming Jia; Rui Sun; Mingguan Yang (Applied Sciences)
Frost mulberry leaves possess significant medicinal and nutritional values and feature extensive resource availability and convenient acquisition. The study investigated the physicochemical structure and functional properties of frost mulberry leaf superfine powder (FMLSP) and the effects of FMLSP on the hypoglycemic activity and gut microbiota of type 2 diabetes mellitus (T2DM) mice. The results indicated that the total flavonoid content of FMLSP reached 91.30 mg/g, with significant inhibitory effects on both α-glucosidase and α-amylase activities. Animal experimental data showed that FMLSP could significantly reduce insulin content, improve insulin resistance, and protect liver and pancreatic tissues in T2DM mice. Meanwhile, FMLSP showed significant effects on lipid metabolism, especially the low-density lipoprotein cholesterol (LDL-C) content in T2DM mice was significantly reduced by 76.22%. In addition, FMLSP has excellent antioxidant effects, which greatly alleviated the oxidative stress phenomenon in T2DM mice, especially the malondialdehyde (MDA) content was significantly reduced by 72.17%. FMLSP also restored the diversity and structure of the gut microbiota, significantly increasing the abundance of beneficial bacteria such as Akkermansia, Lachnospiraceae_NK4A136_group, Alloprevotella, and Lactobacillus in T2DM mice and significantly decreasing the abundance of abundance of harmful bacteria such as Rikenellaceae_RC9_gut_group, Enterorhabdus. These results indicate that FMLSP may serve as a potential dietary intervention for the prevention and treatment of T2DM.